Estimation of the Demand for Local Public Education under a Kinked Budget Constraint - Megna, Richard H.; Lee, Tong Hun (The Review of Economics and Statistics, 1990)
Unlike previous studies on the demand for local public education, this paper applies a minimum likelihood technique, developed for a kinked budget constraint, to the case of Wisconsin school districts and carries out simulations. The results indicate that (1) the bias in estimation under standard econometric techniques is substantial, (2) the so-called flypaper effect indeed exists, and (3) the impacts of grants on expenditures and wealth neutrality are different from those obtained by previous studies. Copyright 1990 by MIT Press.